Presynaptic mGlu1 Receptors Control GABAB Receptors in an Antagonist-Like Manner in Mouse Cortical GABAergic and Glutamatergic Nerve Endings - Vergassola, Matteo; Olivero, Guendalina; Cisani, Francesca; Usai, Cesare; Bossi, Simone; Puliti, Aldamaria; Pittaluga, Anna (Frontiers in Molecular Neuroscience, 2018)
Mouse cortical GABAergic synaptosomes possess presynaptic inhibitory GABAB autoreceptors. Accordingly, (±)baclofen (3 μM) inhibits in a CGP53423-sensitive manner the 12 mM KCl-evoked release of preloaded [3H]GABA. Differently, the existence of presynaptic release-regulating metabotropic glutamate type 1 (mGlu1) heteroreceptors in these terminals is still matter of discussion, although confocal microscopy unveiled the existence of mGlu1α with GABAB1 or GABAB2 proteins in cortical VGAT-positive synaptosomes. The group I mGlu agonist 3,5-DHPG failed to modify on its own the 12 mM KCl-evoked [3H]GABA exocytosis from cortical nerve endings, but, when added concomitantly to the GABAB agonist, it significantly reduced the 3 μM (±)baclofen-induced inhibition of [3H]GABA exocytosis. Conversely, the mGlu1 antagonist LY367385 (0.03–1 μM), inactive on its own on GABA exocytosis, amplified the 3 μM (±)baclofen-induced inhibition of [3H]GABA overflow. The ( ± )baclofen-induced inhibition of [3H]GABA exocytosis was more pronounced in cortical synaptosomes from Grm1crv4/crv4 mice, which bear a spontaneous mutation of the Grm1 gene leading to the functional inactivation of the mGlu1 receptor. Inasmuch, the expression of GABAB2 receptor protein in cortical synaptosomal lysates from Grm1crv4/crv4 mice was increased when compared to controls. Altogether, these observations seem best interpreted by assuming that mGlu1 coexist with GABAB receptors in GABAergic cortical synaptosomes, where they control GABA receptors in an antagonist-like manner. We then asked whether the mGlu1-mediated control of GABAB receptors is restricted to GABAergic terminals, or if it occurs also in other subpopulations of nerve endings. Release-regulating GABAB receptors also exist in glutamatergic nerve endings. (±)baclofen (1 μM) diminished the 12 mM KCl-evoked [3H]D-aspartate overflow. Also in these terminals, the concomitant presence of 1 μM LY367385, inactive on its own, significantly amplified the inhibitory effect exerted by (±)baclofen on [3H]D-aspartate exocytosis. Confocal microscopy confirmed the colocalization of mGlu1 with GABAB1 and GABAB2 labeling in vesicular glutamate type1 transporter-positive particles. Our results support the conclusion that mGlu1 receptors modulate in an antagonist-like manner presynaptic release-regulating GABAB receptors. This receptor–receptor interaction could be neuroprotective in central disease typified by hyperglutamatergicity.